2015
DOI: 10.1055/s-0035-1566743
|View full text |Cite
|
Sign up to set email alerts
|

KLF15 Overexpression Protects β-Aminopropionitrile–Induced Aortic Rupture in Rodent Model via Inhibiting Connective Tissue Growth Factor

Abstract: KLF15 (Krüppel-like factor 15) was reported to be involved in a lot of cardiovascular diseases. Little is known about its role in initiation and development of aortic dissection (AD). Samples of the human aorta were collected during AD surgery and aortic valve replacement. Lentivirus was used for in vitro and in vivo KLF15 overexpression in BAPN (β-aminopropionitrile)-induced rat AD models. The survival times were recorded and compared between the two groups. Autopsy was used for confirming aorta rupture in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…1, 2). In our opinion, these results indicate that transduction does not spread gradually from the intima to the adventitia, but rather that LVs can transduce cells of the outer layers of the vascular wall through additional routes that do not necessarily involve intima transduction, such as potential LV access to adventitia through vasa vasorum [27,28,30].…”
Section: Targeting Of Vascular Cellsmentioning
confidence: 81%
“…1, 2). In our opinion, these results indicate that transduction does not spread gradually from the intima to the adventitia, but rather that LVs can transduce cells of the outer layers of the vascular wall through additional routes that do not necessarily involve intima transduction, such as potential LV access to adventitia through vasa vasorum [27,28,30].…”
Section: Targeting Of Vascular Cellsmentioning
confidence: 81%
“…Increased miR‐145 expression can accelerate VSMC proliferation and ameliorate cell apoptosis by binding to SMAD3 and connective tissue growth factor (CTGF), which can reduce the effect of miR‐145 in the progression of AAD 20 . CTGF, a matricellular protein, can ameliorate aortic remodelling in the rat AD model and participate in the proliferation and apoptosis of VSMCs 68 . In summary, studies on the miR‐145‐CTGF/SMAD3 axis may provide potential therapeutic targets for AAD.…”
Section: Mirnas In Aortic Dissectionmentioning
confidence: 99%
“…Deficiency of the KLF15 repressor inhibited p300-mediated acetylation of p53, and thereby reduced the activity of NF-κB on inflammatory gene promoters [12]. In β-aminopropionitrile-induced rat AD models, the lentivirus was used for in-vitro and in-vivo KLF15 overexpression, which showed that the KLF15 mRNA was increased, whereas CTGFs and its target gene collagens I and III were downregulated [36]. These studies showed that KLF15 played an important role in aorta remodeling and aortic dissection formation.…”
Section: Kruppel-like Factor 15 and Aortic Lesionsmentioning
confidence: 99%